The effect of digital literacy, self-awareness, and career planning on engineering and vocational teacher education students' learning achievement - Soeprijanto Soeprijanto; Aodah Diamah; Rusmono Rusmono (OmniaScience, 2022)
This study aimed to determine the direct and indirect effects of digital literacy, self-awareness, career planning on student achievement of prospective teachers of education and technical and vocational training (TVET). This type of research is ex post facto with quantitative data. The method used was comparative causal differential with path analysis. The problems posed are (1) whether there is a direct effect of digital literacy, self-awareness, career planning on learning achievement, and (2) whether there is an indirect effect of digital literacy and self-awareness on learning achievement. The results showed that (1) Digital Literacy and Self Awareness directly affect Career Planning by 42.8%. (2) Taken together, digital literacy, self-awareness, and career planning directly affect student learning achievement. The effect of these three variables reached 50.9%. (3) The direct effect of digital literacy and self-awareness on learning achievement tends to be dominant compared to the indirect effect through Career planning. The total effect of digital literacy on learning achievement is 0.33, with details of the direct effect of 0.263 and the indirect effect of 0.068 through career planning. The total effect of self-awareness on learning achievement is 0.4809, with further information of the direct effect of 0.345, and the indirect effect of career planning is 0.1359. Research recommendations need to be expanded by adding respondents and job literacy variables among prospective TVET teacher students as independent variables.